Developing "whole school" bystander interventions: The role of school-settings in influencing adolescents responses to dating violence and bullying. (March 2017) - Storer, Heather L.; Casey, Erin A.; Herrenkohl, Todd I.
Abstract: Bystander intervention programs have been introduced as innovative strategies to empower teens to intervene proactively when they witness bullying and dating violence (TDV) in their social environments. While there is promising research on the individual-level factors that influence students' willingness to intervene, there has been limited investigation on how teens' school environments encourage proactive responses. Through analysis of focus group data, this study revealed that teens are reluctant to employ bystander behaviors in any capacity. Some of the school-level factors that influenced their willingness to intervene include: trusting relationships with teachers; the perception that school personnel, rather than students, have more expertise to respond effectively; school environments that were tolerant of dating abuse; and ineffective school policies. Implications for creating "whole-school" responses to bullying and TDV will be discussed. Highlights: Teens are reluctant to intervene as prosocial bystanders in response to dating violence and bullying at schools. School environments are perceived to be particularly tolerant of dating violence. Compared to students, teens believe teachers have more expertise and power to intervene in response to abuse. Partnerships between teachers, students, and administrators are imperative for fostering cultures of responsiveness.